Influence mechanism of mechanical properties and crack formation of CaCO3/PVC composites based on cohesion model. (June 2022) - Luo, Shijun; Pan, Sining; Chang, Hongbin; Zhang, Min; Yu, Wudong; Lai, Zhengsun
Abstract: The influence mechanism and crack formation are the key problems in the study of mechanical properties for CaCO3 /PVC composites. However, experimental methods are usually time consuming and high cost. In this paper, finite element simulation is applied for the study of the mechanical properties of CaCO3 /PVC composites. Firstly, the representative volume elements (RVE) of CaCO3 /PVC composites with various shapes of CaCO3 particle are established. Secondly, the constitutive relation of CaCO3 /PVC composites is proposed based on the cohesion model. Furthermore, the behaviors of CaCO3 /PVC composites under tensile loading are simulated by finite element method. Both the influence mechanism of CaCO3 particle shape and filling mode on the mechanical properties of CaCO3 /PVC composites, and the formation mechanism of internal cracks in the composites are discussed. It can be seen from the simulated results that, the ellipsoid particles with randomly filled shows better properties improvement of the composites. The composites filled with oriented ellipsoid particles present significant directional characteristic of property improvement. In addition, the formation mechanism of internal cracks in the composites is explained from the view of microstructure. The research shows guiding significance for component and morphology optimization of particle filled composites with polymer matrix, which can reduce the research time and cost of new materials effectively. Graphical Abstract: ga1